FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENORE PRIMER PADA MAHASISWI PRODI ILMU KEPERAWATAN INSTITUT CITRA INTERNASIONAL TAHUN 2024: FACTORS RELATED TO THE INCIDENT OF PRIMARY DYSMENORHORE IN NURSING SCIENCE STUDENTS OF THE INTERNATIONAL CITRA INSTITUTE IN 2024 - Muzaimah, Muzaimah; Kusumajaya, Hendra; Hermain, Hermain (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Health problems that can occur in adolescent reproductive health during menstruation include dysmenorrhea or pain during menstruation. Primary dysmenorrhea is dysmenorrhea that begins to be felt since menarche and no abnormalities are found in the reproductive organs or other organs. The purpose of this study was to determine the factors associated with the occurrence of primary dysmenorrhea in female nursing students at the Institut Citra Internasional in 2024. The research design used a quantitative method with an analytical survey method through a cross-sectional research approach and a chi-square test at a confidence level of 95% <α (0.05) with the results in the form of univariate and bivariate analysis. The number of samples is 203, with simple random sampling conducted on May 30 - June 13, 2024. This researcher concluded that Factors Related to the Incidence of Primary Dysmenorrhea in Nursing Science Study Program Students at the Citra Internasional Institute in 2024 were the age of menarche (p = 0.000, POR = 3.154), duration of menstruation (p = 0.000, POR = 15.328), body mass index (BMI) (p = 0.020, POR = 2.179), history of dysmenorrhea (p = 0.000, POR = 8.486). And the most dominant factor is the duration of menstruation. The suggestion in this study is for health institutions to be able to conduct assessments, provide counseling and interventions, especially for adolescent girls, the problem of pain during menstruation and to study more deeply the factors that play a role in menstruation. For female students to study more deeply the risk factors that cause primary dysmenorrhea. For the public, there needs to be additional knowledge about menstrual pain related to reproductive health by seeking references or discussing from various trusted sources Keywords : Primary Dysmenorrhea, Body Mass Index (BMI), Length of Menstruation, Age of Menarche, History of Dysmenorrhe Abstrak Masalah kesehatan yang dapat terjadi pada kesehatan reproduksi remaja pada saat menstruasi salah satunya yaitu dismenorea atau nyeri pada saat menstruasi. Dismenore primer adalah dismenore yang mulai terasa sejak menarche dan tidak ditemukan kelainan dari alat kandungan atau organ lainnya. Tujuan dari penelitian ini adalah untuk mengetahui Faktor-faktor yang berhubungan dengan kejadian dismenore primer pada mahasiswi prodi ilmu keperawatan Institut Citra Internasional Tahun 2024. Desain penelitian menggunakan metode kuantitatif dengan metode survey analitik melalui pendekatan penelitian cross- sectional. Populasi penelitian adalah semua mahasiswa perempuan Prodi Ilmu Keperawatan Institut Citra Internasional Tahun 2024 yang terdata aktif di akademik sebanyak 411 mahasiswi, pengambilan sampel simple random sampling, jumlah sampel 203 mahasiswi. Data dianalisis secara Univariat dan Bivariat menggunakan uji chi square pada tingkat kepercayaan 95% atau α (0,05). Penelitian ini menyimpulkan bahwa Faktor-Faktor yang Berhubungan Dengan Kejadian Dismenore Primer Pada Mahasiswi Prodi Ilmu Keperawatan Institut Citra Internasional Tahun 2024 adalah usia menarche (p=0,000, POR=3,154), lama menstruasi (p=0,000, POR=15,328), indeks masa tubuh (IMT) (p= 0,020, POR=2,179), riwayat dismenore (p= 0,000, POR=8,486), faktor yang paling dominan adalah lama menstruasi. Rekomendasi penelitian ini yaitu bagi institusi kesehatan untuk dapat melakukan pengkajian, memberikan penyuluhan dan intervensi, terutama pada mahasiswi Institut Citra Internasional Bangka Belitung, masalah nyeri pada saat menstruasi dan mahasiswi mempelajari lebih dalam lagi tentang faktor-faktor resiko yang menyebabkan dismenore primer dan lama menstruasi tidak normal pada mahasiswi. Kata Kunci: Dismenore Primer, Indeks Masa Tubuh (IMT), Lama Menstruasi, Usia Menarche, Riwayat Dismenore.